The Use of Mechanisms in Congestion Pricing - Kveiborg, Ole (Proceedings from the Annual Transport Conference at Aalborg University, 2001)
Transport economists have for a long time focussed on efficiency. A means of achieving efficiency is to price transport at its social marginal costs -- using Pigou taxes in the case of externalities. However, it is very difficult to obtain the information needed in order to define correct tax levels. New Road Pricing technological instruments makes it possible to implement marginal cost pricing in transport. However, the question of how to find the right level of Pigou prices remains unresolved. In this paper some of the practical implications of using a new theoretical basis for congestion pricing are analysed.